Synergistic effects of information and cybernetic interaction in civil aviation. Issue 3 (2nd July 2016) - Danik, Yuriy; Hryschuk, Ruslan; Gnatyuk, Sergiy
Abstract: Scientific research on information and cybernetic influence on citizens, society and the whole state is a hot topic of many famous worldwide scientific publications. These studies have become particularly relevant in critical spheres from the viewpoint of security. Civil aviation is one of the most critical spheres. Information and cybernetic actions in civil aviation have been studied separately to date. Known approaches did not allow considering the synergistic effects of information and cybernetic interaction. This factor has adversely affected preventive and countermeasures for minimizing the effects of information and cybernetic threats to aviation subjects. Taking this into account, in the paper, the essence of synergistic effects of information and cybernetic interaction on civil aviation are presented. Also, the methodology for the early detection, assessment and prediction of these effects was developed. The analysis revealed that the study of synergistic effects in civil aviation is an effective controller of nonlinear processes, which can occur as the result of information and cybernetic interaction.